Inventory of Echinodermata in Lendang Luar Beach, North Lombok District - Dewi, Saskia Septina; zahara, asha aulia; aulia, nurul waroatul; nurulfadilah; riandinata, selamet kurniawan; Candri, Dining Aidil; Ahyadi, Hilman (Samota Journal of Biological Sciences, 2024)
Echinoderms are one of the main components of marine biodiversity that play an important role in ecosystem function, especially as aquatic detritus. The purpose of this study was to determine the species of Echinoderms found in Lendang Luar Beach, North Lombok District. The study was conducted in July 2022 using the purposive sampling and free sample collection. Based on the research results, found 12 species from 6 families, namely Deadematidae (Diadema setosum, Echinothrix calamaris, and Echinothrix diadema), Echinometridae (Echinometra oblonga and Heliocidaris crassispina), Holothuriidae (Holothuria tubulosa), Ophiocomidae (Ophiomastix annulosa, Ophiocoma erinaceus, Ophiocoma pusilla, and Ophiocoma scolopendrina), Ophiothrichidae (Macrophiothrix longipeda), and Toxopneustidae (Tripneustus gratilla). O. Annulosa, M. longipeda, and T. gratilla species were found in all stations. M. longipeda had the highest number of individuals. T. gratilla has the most extensive microhabitat because it is found in all types of existing microhabitats.